2011
DOI: 10.5121/ijasuc.2011.2104
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evalution of MANET Routing Protocols using Reference Point Group Mobility and Random WayPoint Models

Abstract: An ad hoc network is often defined as an "infrastructureless" network, meaning a network without the usual routing infrastructure like fixed routers and routing backbones. Typically, the ad hoc nodes are mobile and the underlying communication medium is wireless. Each ad hoc node may be capable of acting as a router.it's charactrizied by multihop wireless connection and frequently changing networks.we compare the performance of on-demand routing protocols for mobile ad-hoc networks are distributed cache updati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…We have observed that, though there is a significant difference between AODV and DSR protocol [8,9,10,11]but by varying a transmission range in between them is not yet analyzed and obtain high throughput. So we have focused on the performance of the protocol by changing a communication range and compute the performance metrics such as packet delivery ratio, average end to end delay, throughput and packet loss [12,13,14].…”
Section: Related Workmentioning
confidence: 99%
“…We have observed that, though there is a significant difference between AODV and DSR protocol [8,9,10,11]but by varying a transmission range in between them is not yet analyzed and obtain high throughput. So we have focused on the performance of the protocol by changing a communication range and compute the performance metrics such as packet delivery ratio, average end to end delay, throughput and packet loss [12,13,14].…”
Section: Related Workmentioning
confidence: 99%
“…It has classified in [20][21][22][23][24] as the fraction among the amount of packets created with the application layer. It has the fraction of data packets send to the target to those created from the starting point.…”
Section: Packet Delivery Ratio (Pdr)mentioning
confidence: 99%
“…Timcenko et al [19] considered RPGM, RWP, GM and MGM mobility models with AODV, DSDV and DSR routing protocols to study PDR and delay.Murthy and Das [20] used varying number of nodes and node speeds, RWP and RPGM mobility models, and AODV and DSR protocols to compare PDR, delay and throughput. Mann and Mazhar [21] suggested the protocol to use for given mobility model, MANET area and other parameters. Barakovic et al [22] created node mobility scenario, varied pause time of the nodes, and did performance evaluation for DSDV, AODV and DSR routing protocols.…”
mentioning
confidence: 99%